VALUE ADDED PERKAWINAN INDUK UDANG WINDU (Penaeus monodon) DARI LOKASI YANG BERBEDA - Cangara, Arie Syahruni; Sudrajat, Iman (Torani Journal of Fisheries and Marine Science, 2016)
The research aim was to compare inner mating of Penaeus monodon and to determine growth of junevile fromcross mating between broodstock from the same and different area. This study was using broodstock from Siwaand Pangkep. Six broodstock from the same and different area would then been mating. Parameters forbroodstock quality were measured including fecundity, period of mating, fertilization, egg diameter and egghatching capability. Parameters for measuring larvae quality were survival rate, number of larvae for eachstage, growth of larvae for each stage. The result showed that the best reproductive potency were fecundity,fertilization and survival rate of larvae that found from mating between female broodstock from Siwa and malebroodstock from Pangkep.Keywords : Source of broodstock, Penaeus monodon, reproductive potency, broodstock and larvae quality